MYOSIN HEAVY CHAIN ISOFORMS, FATTY ACID COMPOSITION, SENSORY EVALUATION AND QUALITY OF CINTA SENESE PIG MEAT - VELOTTO, S.; RABIE ASHKEZARY, M.; DE CAMILLIS, S.; TODARO, A. (Italian Journal of Food Science, 2018)
The aims of this study were to examine the effects of myosin heavy chain (MHC) isoforms on Cinta Senese meat and sensory quality. The research was carried out on 65 pigs and muscle samples characteristics such as MHC isoform, meat quality, fatty acid composition, and sensory were evaluated. The results demonstrated that MHC slow isoform content was significantly correlated with pH24h (r=0.25, P